Optimal state feedback control for wireless networked control systems with decentralised controllers. Issue 6 (1st April 2015) - Wang, Zhuwei; Wang, Xiaodong; Liu, Lihan; Huang, Mo
Abstract : In this study, the design of the optimal decentralised full‐state‐feedback controllers is derived for wireless networked control systems with network‐induced delays. In particular, the authors formulate the optimal decentralised control problem as a non‐cooperative linear quadratic game. Then, the optimal control strategy of each controller is obtained that is based on the current plant state and the last control strategies of decentralised controllers. The proposed optimal decentralised controllers reduce to the known controller under certain conditions. Moreover, the authors illustrate the application of the proposed decentralised state feedback control to load frequency control in power grid systems.